2022
DOI: 10.1002/ijc.34256
|View full text |Cite
|
Sign up to set email alerts
|

Research advances in nanomedicine applied to the systemic treatment of colorectal cancer

Abstract: The systematic treatment of colorectal cancer (CRC) still has room for improvement.The efficacy of chemotherapy, that of anti-vascular therapy, and that of immunotherapy have been unsatisfactory. In recent years, nanomaterials have been used as carriers to improve the bioavailability of anticancer drugs. For the treatment of colorectal cancer, nanodrugs increase the possibility of more precise targeted delivery. However, the actual benefits may cover more aspects. Nanocarriers can produce synergistic effects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 132 publications
0
4
0
Order By: Relevance
“…The innate immune response is activated when synergistic mechanical and thermal FUS effects with immunotherapy, anti-PD-1 antibodies, and CpG are employed [9]. HIFU treatment triggered the maturation of DCs, the concentration of tumor-specific IFNsecreting cells, and augmented effects of cytotoxic T lymphocytes as proposed by initial experimentation [11]. Recent investigations talk about the biological and immunological impacts of mechanical FUS, specifically relating to tumors.…”
Section: Immune Modulation Using Therapeutic Focused Ultrasound In Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…The innate immune response is activated when synergistic mechanical and thermal FUS effects with immunotherapy, anti-PD-1 antibodies, and CpG are employed [9]. HIFU treatment triggered the maturation of DCs, the concentration of tumor-specific IFNsecreting cells, and augmented effects of cytotoxic T lymphocytes as proposed by initial experimentation [11]. Recent investigations talk about the biological and immunological impacts of mechanical FUS, specifically relating to tumors.…”
Section: Immune Modulation Using Therapeutic Focused Ultrasound In Co...mentioning
confidence: 99%
“…As a result, fine-tuning ultrasound exposure parameters is essential to achieve the desired immune response [6]. Research has documented inflammatory responses linked to the NF-κB pathway and macrophage infiltration in the murine colon following LIFU treatment, particularly in scenarios necessitating colorectal cancer opening without notable immune reactions [11]. In colorectal cancer, the implementation of pulsed LIFU treatment through an ultrasound-guided FUS exposure system elicited prolonged elevations in tumor cytotoxic T lymphocytes and the regulatory T lymphocytes ratio relative to control groups [56].…”
Section: Immune Modulation Using Therapeutic Focused Ultrasound In Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…[200] At the same time, some studies have shown that the combined treatment with immune checkpoint inhibitors can get a better curative effect while targeting the target bacteria. [201] Fn can increase the level of immunosuppressive myeloid-derived suppressor cells and inhibit the anticancer immune response in the host. Dong et al used the M13 phage display library to screen phage strains in vitro and obtained phage strains that could specifically bind Fn.…”
Section: Immunotherapymentioning
confidence: 99%